The Efficacy of The Integrated Child Development Services in Perspective to Nutritional Condition and Growth Development - Jemy Elizabeth Joseph; Shiju Mathew (Intelektual Pustaka Media Utama, 2015)
A survey was conducted to assess the nutritional status of children (0-6 years) among 40 Anganwadis in 4 districts of Kerala State registered under the ICDS scheme. A self- prepared structured interview schedule was used. To get the qualitative information of the study anthropometric measures include height and weight were used for assessing nutritional status of the children. The stepwise analysis of two variables height for age and weight for age was applicable on the basis of Waterlow’s and Gomez’ classification. To examine the relationship between nutritional status of the child and selected variable that affects nutritional status of children, Chi-square test was employed. Based on Gomez’ classification, out of 400 children, only 300 (75.0%) of children received supplementary nutrition through ICDS out of which 250 (62.5%) children were normal while 50 (12.5%) were underweight. Based on Waterlow’s classification out of 400 children, only 290 (72.5%) of children received supplementary nutrition through ICDS out of these children 200 (50 %) were normal while 90 (22.5%) were stunted. It can thus be concluded that majority of children were normal who received supplementary nutrition through ICDS.